Effect of total solids content in feed emulsion on the physical properties and oxidative stability of microencapsulated kenaf seed oil - Ng, Shy-Kai; Choong, Yew-Hong; Tan, Chin-Ping; Long, Kamariah; Nyam, Kar-Lin (Elsevier, 2014)
Kenaf (Hibiscus cannabinus L.) seed oil has high potential to be used as edible oil. Despite the high content of polyunsaturated fatty acids, one of the major complications in commercialisation kenaf seed oil is its rapid oxidation, which leads to the production of undesirable toxic substances such as peroxides. The objective of this study was to investigate the effect of total solids content (TSC) on the oxidative stability of microencapsulated kenaf seed oil (MKSO) and to compare its oxidative stability with bulk kenaf seed oil upon accelerated storage. Microcapsules with 20%, 30% and 40% total solids content were prepared. Physical properties, such as the emulsion characteristics and microcapsules characteristics were also studied. Results showed that bulk kenaf seed oil was oxidised to a greater extent compared to the microencapsulated samples. The results showed that 40% total solids content microcapsules had the lowest peroxide value (PV), p-anisidine value (AnV), total oxidation (TOTOX) value and free fatty acid (FFA) value, which were 3.70 ± 0.83 meq O2/kg oil, 16.12 ± 0.19, 23.52 ± 1.67 and 2.54 ± 0.06%, respectively. The microencapsulation of kenaf seed oil showed protective effect against lipid oxidation.